EFEKTIVITAS PENGGUNAAN E-TILANG TERHADAP PELANGGARAN LALU LINTAS DI KOTA PEKANBARU - M Hafidh Novaldi; Mukhlis R; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The application of e-tickets is an effective option to achieve the target in theimplementation of tickets for traffic violators so that it is expected to be a solutionin solving unwanted things when prosecution takes place. Basically, the issuing ofa ticket and the trial mechanism is similar to a regular ticket. What makes thedifference is the presence of an electronic recorder to record driver errors. Article272 Paragraph (1) of the Law on Road Traffic and Transportation can useelectronic equipment, which is further regulated in Article 23 of the GovernmentRegulation of the Republic of Indonesia Number 80 of 2012 which stipulates thatthe prosecution of traffic and road transportation violations.The objectives in writing this thesis, namely: First, For knowingeffectiveness from e -ticket in reduce number violation then traffic at the policestation Pekanbaru . Second, For knowing obstacle and effort resolve obstacle thein enforcement e - ticket system on moment this , use smoothness enforcement e -ticket system in the future come . The type of legal research used by the author isa sociological legal research type. This sociological research is a type of researchthat is viewed from a legal point of view.From the results of the study, it was found that the electronic ticket receiveda good response and the community agrees with the existence of an E-ticket inPekanbaru City, because the existence of an E-ticket This ticket can increasepublic awareness and awareness as well more obedient to traffic rules eventhough there are no police. Next E-Ticket can also decrease the number of trafficviolations in Pekanbaru City and E-ticketing system is more transparent becausethere is recorded evidence and fines the money is sent directly to the State, sothere is very little chance of there is bribery. Barriers found in the implementationof E-tickets in handling traffic violations concerning the condition of humanresources in the implementing the synergy of public services, the ticketing systemis still not optimal implemented from the aspect of quantity and quality ofpersonnel. Author's Suggestions, First, hold a socialization regarding the e-ticketsystem from enforcement officers law.Keywords: E-Tickets-Traffic Violations-Pekanbaru Police